New orally active anticoagulant agents for the prevention and treatment of venous thromboembolism in cancer patients - Gerotziafas GT; Mahé I; Elalamy I (Dove Medical Press, 2014)
Grigoris T Gerotziafas,1,2 Isabelle Mahé,3 Ismail Elalamy1,21Service d'Hématologie Biologique, Hôpital Tenon, Hôpitaux Universitaires Est Parisien Assistance Publique Hôpitaux de Paris, Paris, France; 2ER2UPMC, Faculté de Médecine Pierre et Marie Curie, Université Paris VI, Paris, France; 3Service de Médecine interne, Hôpital Louis Mourier, Universite´ Paris 7, Assistance Publique Hôpitaux de Paris, EA REMES Université Paris Diderot, Sorbonne Paris Cité, Paris,FranceAbstract: Patients with cancer have a 6–7-fold higher risk of venous thromboembolism (VTE) as compared with non-cancer patients. Effective and safe anticoagulation for the prevention and treatment of VTE is the cornerstone of the management of patients with cancer, aiming to decrease morbidity and mortality and to improve quality of life. Unfractionated heparin, low molecular weight heparins, fondaparinux and vitamin K antagonists (VKAs) are used in the prevention and treatment of VTE in cancer patients. Heparins and fondaparinux are administered subcutaneously. VKAs are orally active, but they have a narrow therapeutic window, numerous food and drug interactions, and treatment requires regular laboratory monitoring and dose adjustment. These limitations among others have important negative impact on the quality of life of patients and decrease adherence to the treatment. New orally active anticoagulant (NOAC) agents are specific inhibitors of activated factor Xa (FXa) (rivaroxaban and apixaban) or thrombin (dabigatran). It is expected that NOACs will improve antithrombotic treatment. Cancer patients are a particular group that could benefit from treatment with NOACs. However, NOACs present some significant interactions with drugs frequently used in cancer patients, which might influence their pharmacokinetics, compromising their efficacy and safety. In the present review, we analyzed the available data from the subgroups of patients with active cancer who were included in Phase III clinical trials that assessed the efficacy and safety of NOACs in the prevention and treatment of VTE. The data from the Phase III trials in prophylaxis of VTE by rivaroxaban or apixaban highlight that these two agents, although belonging to the same pharmacological group (direct inhibitors of factor Xa), have substantially different profiles of efficacy and safety, especially in hospitalized acutely ill medical patients with active cancer. A limited number of patients with VTE and active cancer were included in the Phase III trials (EINSTEIN, AMPLIFY, and RE-COVER) which evaluated the efficacy and safety of NOACs in the acute phase and secondary prevention of VTE. Although, from a conceptual point of view, NOACs could be an attractive alternative for the treatment of VTE in cancer patients, the available data do not support this option. In addition, due to the elimination of the NOACs by the liver and renal pathway as well as because of their pharmacological interactions with drugs which are frequently used in cancer patients, an eventual use of these drugs in cancer patients should be extremely cautious and be restricted only to patients presenting with contraindications for low molecular weight heparins, fondaparinux, or VKAs. The analysis of the available data presented in this review reinforces the request for the design of new Phase III clinical trials for the assessment of the efficacy and safety of NOACs in specific populations of patients with cancer.Keywords: rivaroxaban, apixaban, dabigatran, antithrombotic treatment